2015
DOI: 10.1021/acs.joc.5b00541
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-Arylnaphtho[2,3-b]phospholes and 2-Arylbenzo[b]phospholes: Effects of 2-Aryl Groups and Fused Arene Moieties on Their Optical and Photophysical Properties

Abstract: Suzuki-Miyaura cross-coupling reactions were used in the divergent synthesis of a series of 2-arylnaphtho[2,3-b]phosphole P-oxides and their benzo[b]phosphole counterparts. We elucidated the electronic and steric effects of the 2-aryl groups and fused arene moieties on the optical and photophysical properties of these two types of phosphole-based π-systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 44 publications
(36 reference statements)
2
34
1
1
Order By: Relevance
“…The phosphindolium salts showed Φ F in the range from 70 % ( 2 h ) to 97 % ( 5 b ) [88 % ( 2 a ), 84 % ( 2 b ), 83 % ( 2 e ), 76 % ( 5 a ), 83 % on average]. The values are comparable to those reported for phosphindole oxide structures …”
Section: Methodssupporting
confidence: 68%
“…The phosphindolium salts showed Φ F in the range from 70 % ( 2 h ) to 97 % ( 5 b ) [88 % ( 2 a ), 84 % ( 2 b ), 83 % ( 2 e ), 76 % ( 5 a ), 83 % on average]. The values are comparable to those reported for phosphindole oxide structures …”
Section: Methodssupporting
confidence: 68%
“…Third, upon increasing solvent polarity,t he emission maximum undergoes as ignificant bathochromic shift, with the color of the emitted light changing from bluish green to reddish orange.T aking advantage of these features,w er ecently developed the corresponding 3-phenyl-substituted derivative Ph-Bphox and demonstrated its application as ap olarity-sensitive probe. [13] These compounds were synthesized from the 3-bromo-substituted benzo-and naphthophosphole oxides 2a and 2b as key precursors, which were readily synthesized by the previously reported intramolecular trans-halophosphanylation of the corresponding phosphanylsubstituted diarylacetylenes (Scheme 1). In the course of this study anonbridged naphthophosphole derivative was reported by Matano and co-workers.…”
mentioning
confidence: 99%
“…In the course of this study anonbridged naphthophosphole derivative was reported by Matano and co-workers. [13] These compounds were synthesized from the 3-bromo-substituted benzo-and naphthophosphole oxides 2a and 2b as key precursors, which were readily synthesized by the previously reported intramolecular trans-halophosphanylation of the corresponding phosphanylsubstituted diarylacetylenes (Scheme 1). [14] Ther eduction of 2a and 2b with HSiCl 3 followed by halogen-lithium exchange with tBuLi produced the corresponding lithiated intermediates.…”
mentioning
confidence: 99%